2021
DOI: 10.1051/e3sconf/202124604005
|View full text |Cite
|
Sign up to set email alerts
|

Data-driven analysis of electricity use for office buildings: a Norwegian case study

Abstract: Buildings are major consumers of primary energy and main contributors to carbon emission. To improve energy efficiency, it is essential to understand the characteristics of energy use in buildings. This study uses an in-use office building with digital systems for monitoring and control in Trondheim, Norway, as the study case. Based on data collected from this office building, a data-driven analysis was conducted to capture the characteristics of electricity use of different parts in the office building. The a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…Commercial smart energy meter According to the study found in [85], there is a noticeable correlation between occupancy and the amount of electricity consumed in various areas of a building, including office space, corridors, and meeting rooms. The authors of [86] proposed a system to predict room occupancy using only data from smart meters to predict whether a room is occupied.…”
Section: Iot-based Smart Energy Metermentioning
confidence: 99%
“…Commercial smart energy meter According to the study found in [85], there is a noticeable correlation between occupancy and the amount of electricity consumed in various areas of a building, including office space, corridors, and meeting rooms. The authors of [86] proposed a system to predict room occupancy using only data from smart meters to predict whether a room is occupied.…”
Section: Iot-based Smart Energy Metermentioning
confidence: 99%